Combining environmental and socioeconomic data to understand determinants of conflicts in Colombia - Fiandrino, Stefania; Cattuto, Ciro; Paolotti, Daniela; Schifanella, Rossano (Frontiers in Big Data, 2023)
Conflicts cause immense human suffering, violate human rights, and affect people’s stability. Colombia is affected for decades by a high level of armed conflicts and violence. The complex mosaic of determinants of conflicts involves the political and socio-economic situation, the drug trafficking in the Colombian economy, and the natural disasters affecting the country. In this work, we aim to evaluate the role of the socioeconomic and environmental determinants of conflicts in the Colombian context. To achieve these aims, we apply a spatial analysis to explore patterns and identify areas that suffer from high levels of conflict. We investigate the role of determinants and their relationship with conflicts through spatial regression models. In this study, we do not consider only the entire Colombian territory, but we extend the analysis to a restricted area (Norte de Santander department) to explore the phenomena locally. Our results show that surprisingly socioeconomic variables present very little relationship with conflicts, while natural disasters and cocaine areas have high significance. Despite some variables seeming to be the more informative to explain the process globally, they highlight a strong relationship for only a few specific areas while considering a local analysis. This result proves the importance of moving to a local analysis to strengthen our understanding and bring out additional information. Finally, by comparing two spatial regression models, we notice a possible diffusion process of conflicts and the presence of spillover effects among regions.